GENERATING MODELS OF SOFTWARE SYSTEMS DURING EXPLORATORY - Akreen M. Saleh; Moayad Y. Potrus (Zanco Journal of Pure and Applied Sciences, 2020)
One of the major parts of the software testing is event-driven software (EDS), all actions of the software come from events. Interaction of the user to the graphic user interface (GUI) of the web and desktop applications will generate events, or for the embedded systems events and signals received from equipment, these are examples of Event-Driven Software. using EDS for software testing gives to the software tester a great result to test software because it generates a large number of events that could be cover most of the EDS's area. In this paper, an automated full-model and sub-model generation have been introduced during the system under testing, it produces test cases of websites to overcome faults and long time-consuming. The stage of the testing procedure includes generating full-model of the websites then extracting sub-model from the full-model in the next stages, test cases generated with path coverage. The proposed testing procedure has been analyzed with the four case studies consisting of Fault Detection and Fault Detection Effectiveness. Has been testing with a manual testing method and it proved its efficiency regarding test generation and time. Further, the sub-model test generation provides more accurate test case suite generation than full-model testing.